Michel Henry's notion of bodily-ownness in the context of the ecological crisis - Lind, Andreas Gonçalves (2022)
Despite the suspicions of Gnosticism that have been cast against Michel Henry’s phenomenology, the truth is that his approach in no way belittles the earth, the nature we inhabit. The purpose of this article is to sketch an eco-phenomenology from Henry’s notion of bodily-ownness. In this sense, I show how Henry defends an intimate and intrinsic connection between the human and nature that risks being severed by the imposition of scientistic ideology. In doing so, an integral ecology emerges from Henry’s radical phenomenology. On the one hand, human beings shall abandon their selfish way of life, in the sense of ceasing to want to dominate, control and transform the world at will. On the other hand, they do so in order to regain their original connection with nature, where they exist in a radical passivity in which life is given to them and is realized more fully as a person in harmony with the earth. In this sense, contrary to some current ecological movements, the ecology that arises from Henry’s approach does not set human beings against nature. In fact, in order for nature to be respected, human beings do not have to disappear, withdraw or stop progressing in the life proper to them.